Service Quality On Electricity Customer Satisfaction Prepay In North Gunungsitoli District - Zega, Orsinil Harfian; Telaumbanua, Eliagus; Waruwu, Meiman Hidayat; Telaumbanua, Wahyutra Adilman (PT. Banjarese Pacific Indonesia, 2024)
The purpose of the study was to determine the Quality of Service affecting Prepaid Electricity Customer Satisfaction in North Gunungsitoli District, Gunungsitoli City, to realize this goal, data collection techniques were carried out by distributing questionnaires to respondents of prepaid electricity customers. This type of research is quantitative based on obtaining data in the form of numbers obtained by distributing questionnaires. From the results of the hypothesis test (t test) it was found that the accepted hypothesis was ha, where there was an influence of service quality on prepaid electricity customer satisfaction in North Gunungsitoli District, Gunungsitoli City, and from the results of the Determination coefficient test obtained a value of 71.1%. This can be interpreted that the satisfaction of Prepaid Electricity customers in North Gunungsitoli District, Gunungsitoli City is influenced by service quality by 71 percent. Based on the results of the T Variable X test of service quality, a calculated value = 7.515 was obtained with a signification level of 0.000. Using a signification limit of 0.05 we get a table t of 1.697. Which signifies that tcount > t table, which means Ho rejected Ha accepted.